Effects of dietary fat source on lutein, zeaxanthin and total carotenoids content of the egg yolk in laying hens during the early laying period - Papadopoulos, G A; Chalvatzi, S; Kopecký, J; Arsenos, G; Fortomaris, P D (British poultry science, 2019)
1. The study was conducted to investigate the effects of different dietary levels of an unsaturated or saturated fat source and the effects of different dietary energy levels in laying hen diets on the carotenoid content of the egg yolk. 2. Seventy-two ISA Brown laying hens aged 22 weeks old were allocated, for a 10 week period, to three treatments: control diet (HE group) with a 3.4% supplemented fat containing 2.1% soybean and 1.3% palm oil as fat sources and a ratio of unsaturated to saturated fatty acid (u/s) of 3.33; a lowered energy diet with 2.4% supplemented fat containing 1.4% soybean and 1.0% palm oil and u/s of 3.41 (LE+high u/s); a lowered energy diet with 2.4% supplemented fat containing 0.5% soybean and 1.9% palm oil and a u/s of 2.39 (LE+low u/s). A marigold plant extract supplement was used as a source of lutein. 3. Performance parameters (feed consumption, feed conversion, body weight), egg production rate and egg quality parameters were similar between treatments. Dietary fat digestibility at the middle of the study period was not different. Egg yolk total fat content was similar in all treatments at the middle and at the end of the study period. 4. Lutein, zeaxanthin, cis-lutein and total carotenoids content were significantly lower in eggs produced from the LE+low u/s group compared to those from the HE and the LE+high u/s groups (P < 0.01 for all parameters). 5. It was concluded that feeding laying hens with a diet containing 1% less supplemented fat and a lower u/s ratio compared to a control diet and to a diet with 1% less supplemented fat with a higher u/s ratio resulted in a significant reduction of carotenoid expression in the egg yolk at the end of experimental period. Performance and egg quality parameters were not affected by treatments.
Keywords: potravní doplňky; Dietary Supplements; Carotenoids; Lutein; Egg Yolk; vaječný žloutek; lutein; dietní tuky; Dietary Fats; náhodné rozdělení; Animal Feed; zvířata; Animals; vztah mezi dávkou a účinkem léčiva; Dose-Response Relationship, Drug; Zeaxanthins; Female; karotenoidy; Random Allocation; Chickens; kur domácí; dieta; krmivo pro zvířata; ženské pohlaví; Diet; zeaxanthiny